Profile of Cognitive Impairement in Patients with Brain Tumors in Dr. Moewardi Hospital, Surakarta - Hapsari, Maria Yosita Ayu; Ilyas, Muhana Fawwazy; Ristinawati, Ira; Stepvia, Stepvia; Novika, Revi Gama Hatta (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Brain tumor is a disease that is difficult to treat and causes high morbidity and morta¬lity. One of the clinical manifestations of brain tumors is cognitive impairment which is the most common neurological problem. The aim of this study is to determine the profile of cognitive impairment in patients with brain tumors.Subjects and Method: The design of this study was a retrospective cross-sectional using secondary data from the Neurology Polyclinic of RSUD Dr. Moewardi in January 2021-March 2022. The subject was diagnosed with a brain tumor based on anamnesis, physical examination, and neuroimaging. Cognitive impairment was inferred through the MoCA-Ina test. The analysis used was univariate descriptive analysis, independent T test, Mann-Whitney test, and Pearson correlation test.Results: There were 29 subjects with a mean MoCA-Ina score (17.97). Primary brain tumors (79.3%), more than metastatic tumors. The majority of patients were diagnosed with meningioma (55.2%). This study showed that there were differences in abstraction scores (p=0.015) and total MoCA-Ina scores (p=0.042) between patients with tumors located in the temporal lobe and non- temporal lobe; differences in abstraction scores (p=0.034) and orientation scores (p=0.042) between patients with supratentorial and infratentorial tumors; and differences in memory scores (p=0.028) between patients with and without radiation history. In addition, this study also found an association between the number of lobes affected by brain tumors with attention score (p=0.027; r=-0.409), abstraction score (p=0.004; r=-0.524), orientation score (p=0.021; r=-0.426), and the total score of MoCA-Ina (p=0.018, r=-0.435).Conclusion: There is an association between brain tumors and cognitive impairment which is concluded through the MoCA-Ina test. The clinical manifestations of cognitive impairment in the patient are in accordance with the neuroanatomical function of the brain affected by the lesion.Keywords: Cognitive, Tumor, MoCA-InaCorrespondence: Maria Yosita Ayu Hapsari. Department of Neurology, Faculty of Medicine, Universitas Sebelas Maret/ Moewardi Hospital, Indonesia. Email: ayositahapsari@gmail.com. Phone: 0813 3155 5412.Indonesian Journal of Medicine (2022), 07(02): 242-250https://doi.org/10.26911/theijmed.2022.07.02.12